FAKTOR PENYEBAB KEJADIAN ASAM URAT PADA LANSIA - Meilantika, Ayu Diana; Putri, Satiti Kawuri; Mulat, Trimaya Cahya; Lestari, Dwi; Nurpratama, Widya Lestari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
High uric acid levels in the elderly can be a risk indicator for various chronic diseases, including heart disease and kidney disease. The problem is that out of 798 elderly people who visit the Berseri Pangkalan Kerinci Health Center, 148 elderly people suffer from gout. This study aims to determine the factors associated with uric acid levels in the elderly at the Berseri Pangkalan Kerinci Health Center. Research is quantitative with a cross sectional approach. The population was all the elderly who visited Berseri Pangkalan Kerinci as many as 148 people. The sample size of 108 respondents was taken using purposive sampling technique. The research measuring instrument is a questionnaire. Data analysis with chi square test. The results showed that the majority of IMT respondents were not obese as many as 62 respondents (57.4%), low purine diet 76 respondents (70.4%), no genetic history of gout 59 respondents (54.6%) and normal uric acid levels were 57 respondents (52.8%). There is a relationship between BMI (p = 0.008) and diet (p = 0.007) with uric acid levels in the elderly. There is no genetic factor relationship (p = 0.307) with uric acid levels in the elderly. It is recommended for the elderly to be able to have a healthy diet, do physical activities such as exercise and maintain ideal body weight to avoid various diseases, one of which is gout.Keywords: Uric Acid, BMI, Elderly, Diet